Optimizing blood pressure control in hypertension: The need to use ABPM. (April 2013) - Schmieder, Roland E.; Lehmann, Marina V.; Schmidt, Stephanie
Abstract Hypertension is the most prevalent, treatable cause of cardiovascular (CV) disease. Patients with hypertension and one or more comorbidities increasingly form a significant part of the primary care practitioner's caseload. The emphasis on intensive blood pressure (BP) lowering has softened, encouraging any degree of BP lowering, since any fall in BP is beneficial for reducing CV risk. Consistency of BP control during long-term therapy (i.e. low visit-to-visit variability) and decreasing BP variability over 24-h may be as, if not more, important than degree of BP lowering per se. Fluctuations in BP between visits as well as within a 24-h period have been associated with increased CV risk. Ambulatory BP monitoring (ABPM) is a crucial element of the clinician's armamentarium not only for assessing the "true" BP load and fluctuations under real-life conditions but for identification of various abnormal BP patterns that may require attention, including white- coat hypertension, masked hypertension, non-dipping and the morning BP surge. ABPM provides accurate assessment of treatment effectiveness over 24-h and may lead to better tailoring of therapy. This article reviews the benefits of ABPM and discusses the importance of selecting long-acting antihypertensive agents for optimizing BP control.